Associations among measures of sequential processing in motor and linguistics tasks in adults with and without a family history of childhood apraxia of speech: A replication study. - Button, Le; Peter, Beate; Stoel-Gammon, Carol; Raskind, Wendy H. (Clinical Linguistics & Phonetics, 2013)
The purpose of this study was to address the hypothesis that childhood apraxia of speech (CAS) is influenced by an underlying deficit in sequential processing that is also expressed in other modalities. In a sample of 21 adults from five multigenerational families, 11 with histories of various familial speech sound disorders, 3 biologically related adults from a family with familial CAS showed motor sequencing deficits in an alternating motor speech task. Compared with the other adults, these three participants showed deficits in tasks requiring high loads of sequential processing, including nonword imitation, nonword reading and spelling. Qualitative error analyses in real word and nonword imitations revealed group differences in phoneme sequencing errors. Motor sequencing ability was correlated with phoneme sequencing errors during real word and nonword imitation, reading and spelling. Correlations were characterized by extremely high scores in one family and extremely low scores in another. Results are consistent with a central deficit in sequential processing in CAS of familial origin.